Metabolomic profiling of lung function in Costa-Rican children with asthma - Kelly, Rachel S. (Biochim Biophys Acta, 2017)
BACKGROUND: The development of novel therapeutics and treatment regimens for the management of asthma is hindered by an incomplete understanding of its heterogeneous nature and pathophysiology. Metabolomics can provide an integrated and global profile of a biological system in a dysregulated state, making it a valuable tool to identify biomarkers along the disease development pathway and to understand the biological mechanisms driving that pathway. METHODS: Liquid Chromatography-Mass spectrometry metabolomic profiling was conducted on plasma samples provided at recruitment for 380 children with asthma from the ‘Genetic Epidemiology of Asthma in Costa Rica Cohort’. Metabolites associated with three clinical characteristics of asthma severity (i) airway hyper-responsiveness (AHR) (ii) percent-predicted forced expiratory volume in one second/forced vital capacity ratio (FEV(1)/FVC), and (iii) FEV(1)/FVC post-bronchodilator were identified and their discriminatory ability assessed. Metabolite set enrichment analyses was applied to explore the biology underlying these relationships. RESULTS: AHR was associated (p<0.05) with 91 of 574 metabolites (15.9%), FEV(1)/FVC pre-bronchodilator with 102(17.8%), and FEV(1)/FVC post-bronchodilator with 155 (27.0%). The findings suggest these characteristics capture some common and some distinct phenotypic aspects of lung function; glycerophospholipid, linoleic acid and pyrimidine metabolism were common to all three characteristics. The corresponding metabolomic profiles showed moderate but robust discriminatory ability. CONCLUSIONS: The results confirm the existence of an asthma severity metabolome. However, differences in the metabolomic profiles of the three lung function characteristics studied, suggest that refinement of both phenotype classification and metabolite selection should be a priority as the field of asthma metabolomics progresses.